2017
DOI: 10.1590/s1980-220x2016039403224
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive aspects and knowledge of family planning among women with Acquired Immunodeficiency Syndrome

Abstract: Objective:To analyze the reproductive aspects and knowledge of family planning among women with Acquired Immunodeficiency Syndrome (AIDS). Method: Crosssectional and descriptive study carried out from January to December, 2015, in the outpatient care of infectious disease unit in a hospital located in Fortaleza, Ceará. Data were collected through a form applied by interview in a private setting. Results: 102 women participated in the study. Most were aware that they were serologically positive with human immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…This study depicted similar findings in sociodemographic characteristics of the respondents when compared with similar previous studies 10,12,21. This implies that WLHIV have similar sociodemographic characteristics irrespective of the location of the study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study depicted similar findings in sociodemographic characteristics of the respondents when compared with similar previous studies 10,12,21. This implies that WLHIV have similar sociodemographic characteristics irrespective of the location of the study.…”
Section: Discussionsupporting
confidence: 90%
“…Having many children by WLHIV may be related to knowledge about pregnancy risks HIV-positive women are exposed to during pregnancy. Prior related studies have reported similar results in Ethiopia,24 Ghana,21 and Brazil 25. Hence, there may be need to include importance of having very few children in counselling WLHIV.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, a third of them revealed they had received reproductive planning guidance and were unaware of prophylaxis measures for vertical HIV transmission. Regarding the serology of couples and conception, women believed seroconcordant couples could have children and serodiscordant couples could not (9) .…”
Section: Resultsmentioning
confidence: 99%
“…This context leads to discussions about sexual and reproductive health and includes the problem arising from the diagnosis of HIV infection, which in turn, imposes the need for planning with use of biotechnologies, such as assisted human reproduction (AHR) (7) , how to protect sexual transmission (8) and prophylaxis of vertical transmission of the virus when the woman is HIV positive. There is also the need to know the couple's serostatus (9) -seroconcordant, when both live with HIV, or serodiscordant, when only one partner lives with the virus, among other facts.…”
Section: Introductionmentioning
confidence: 99%